Role of microfat and nanofat for acne scars and skin aging: a case report - I Gusti Nyoman Darmaputra (Journal of Cosmetic Medicine, 2025)
Microstructure in skin aging shows reduced collagen production, degenerated elastin, and atrophic subcutaneous adipose tissue that resulting in stiffness, decreased elasticity, and deepening wrinkles. Autologous fat grafting has contributed to addressing age-related volume loss in skin aging by serving as biological and permanent filler material and acne scars rejuvenation. Microfat offers soft tissue structural filling effect, whereas nanofat enhances skin quality and promotes tissue regeneration in applications of scars rejuvenation. Here I present a 35-year-old male presented with facial aging and acne scars. The patient underwent autologous fat grafting procedure using fat harvested from the abdomen. The main objective is to fill the loss soft tissue structural and promote the regeneration of acne scars. The technique of choice for fat harvesting is syringe aspiration with a 10-20 ml Luer-Lok syringe attached to a harvesting cannula. Within the syringe, the yellow adipose grafts quickly separate from the underlying infranatant fluid according to their density, resulting in the grafts floating in the middle, on top of which is the lipid layer. The emulsification can be formed into the microfat or nanofat. The procedure also incorporated subcision for acne scars. Improvement can be seen within a few days post-surgery. This case demonstrated the effectiveness combination of microfat and nanofat for skin aging and acne scars rejuvenation. Autologous fat grafting is a safe and alternative option for facial rejuvenation and acne scar treatment with minimal side effects and complications. This technique could also be combined with other modalities for better outcomes.